PENGARUH ALIRAN MODAL ASING TERHADAP PERTUMBUHAN EKONOMI DI ASIA - Shafiah Meike Serepina Pasaribu (Bina Ekonomi, 2018)
ABSTRACTCapital account liberalization possibly promotes growth. However, the policy is considered a source of crisis. This study examines the effect of foreign capital inflows, in terms of FDI (Foreign Direct Investment) and FPI (Foreign Portfolio Investment), on economic growth and examines the determinants of capital flows to selected Asian countries over the 1998-2017 period. Based on the Two-Stage Least Square result, higher USA growth rates and lower interest rate differential are push factors of FDI, while domestic economic growth is a pull factor of FDI and FPI. The long-run FDI positively and significantly affects growth, whereas FPI has a negative but non-significant effect. The result indicates that an increase in growth can boost FDI inflows thereupon leads to higher growth. Keywords: economic growth; capital flows; liberalization